An examination of the elite development pathways for male golfers in Ireland. Issue 6 (2nd November 2019) - Kitching, Niamh; Campbell, Mark
ABSTRACT: Research question: In recent years, Irish men's professional golf has enjoyed global success, resulting in an increased focus on golfer development and talent pathways in Ireland. Using the SPLISS model as a guiding framework, the aim of this study is to examine the organisational factors in the male amateur high-performance golf pathway that contribute to or inhibit international sporting success. Research methods: A mixed-methods approach was employed consisting of player ( N  = 597; n  = 109) and coach ( N  = 27; n  = 27) questionnaires, focus groups and semi-structured qualitative interviews with junior ( n  = 5) and adult ( n  = 2) players, parents ( n  = 2), coaches ( n  = 27) and physiotherapists ( n  = 2). Results and findings: While the system performed well in areas such as coaching and competition, a lack of programme planning and organisation resulted in poor communication and incoherent policy from regional to national level. Implications: This research represents a significant move forward in terms of a more detailed and nuanced understanding of the (pre) elite development pathways for golfers. A contribution is made to the small number of country/sport-specific studies using the SPLISS model focusing on the meso-organisational level.